1995
DOI: 10.1016/0920-1211(95)00032-6
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of intracortical GABAergic inhibition in a rat model of absence epilepsy

Abstract: The WAG/Rij rat strain is characterized in its EEG by the manifestation of spike-wave discharges which resemble in their spontaneous appearance and pharmacological sensitivity the absence epilepsy observed in humans. In order to test the hypothesis whether cellular intrinsic membrane and/or synaptic network properties in the neocortex are modified in this form of epilepsy, we analyzed with extra-and intracellular recording techniques the functional status of neocortical slices obtained from adult epileptic WAG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(63 citation statements)
references
References 37 publications
7
55
0
1
Order By: Relevance
“…Experimental evidence obtained to date from in vitro slice studies indicates that epileptic WAG/Rij neocortical neurons present with: (i) marked reduction in I h (a cation current that is known to modulate neuron excitability and rhythmicity) (Strauss et al, 2004), (ii) decreased function of GABA A receptor-mediated post-synaptic inhibition (Luhmann et al, 1995) and (iii) increased NMDA receptor-mediated events leading to prolonged depolarizing responses and to action potential discharge (Luhmann et al, 1995;D'Arcangelo et al, 2002;D'Antuono et al, 2006). The latter mechanism has also been identified in vivo both in WAG/Rij (Peeters et al, 1989) and GAERS (Pumain et al, 1992) animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental evidence obtained to date from in vitro slice studies indicates that epileptic WAG/Rij neocortical neurons present with: (i) marked reduction in I h (a cation current that is known to modulate neuron excitability and rhythmicity) (Strauss et al, 2004), (ii) decreased function of GABA A receptor-mediated post-synaptic inhibition (Luhmann et al, 1995) and (iii) increased NMDA receptor-mediated events leading to prolonged depolarizing responses and to action potential discharge (Luhmann et al, 1995;D'Arcangelo et al, 2002;D'Antuono et al, 2006). The latter mechanism has also been identified in vivo both in WAG/Rij (Peeters et al, 1989) and GAERS (Pumain et al, 1992) animals.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent evidence points to the perioral area of the somatosensory cortex as the site of initiation of generalized SW activity in both WAG/Rij and GAERS epileptic animals (Meeren et al, 2002;Manning et al, 2004). Several in vivo and in vitro studies have shown that neocortical hyperexcitability in these genetic models is caused by changes in intrinsic (Strauss et al, 2004;Klein et al, 2004) and synaptic mechanisms (Peeters et al, 1989;Pumain et al, 1992;Luhmann et al, 1995;D'Arcangelo et al, 2002;Pinault, 2003;D'Antuono et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The cortical hyperexcitability in WAG/Rij rats, measured by extra-and intracellularly recorded synaptic responses, is probably due to a decrease in GABA-mediated inhibition leading to the hypothesis that the GABA effects on SWDs may depend on regional processes and are not homogeneous within the brain (Luhmann et al, 1995). Interestingly, Merlo et al indicate that these molecular changes are not seen in young (about 60days old) WAG/Rij rats that do not yet present SWDs (Merlo et al, 2007).…”
Section: Gabamentioning
confidence: 99%
“…Altered GABA A receptor function has been described in the cerebral cortex and thalamus of WAG/Rij rats and may contribute to abnormal brain states of absence epilepsy (D'Antuono et al, 2006;Luhmann et al, 1995). In WAG/Rij rats, GABAergic inhibition is reduced in upper-layer frontal cortical neurons (Luhmann et al, 1995), and GABA A receptor-mediated fast hyperpolarizing inhibitory postsynaptic potentials (IPSPs) show decreased peak conductances in deeper-layer neurons (D'Antuono et al, 2006). WAG/Rij rats in comparison to Wistar rats, exhibited a significant reduction in the efficiency of intracortical GABAergic inhibition concomitant with hyperexcitability (Luhmann et al, 1995) and interestingly, many cortical areas are lacking parvalbumin-containing interneurons.…”
Section: Gabamentioning
confidence: 99%
“…In line with this view, recent studies in slices of the ferret lateral geniculate nucleus have shown that the frequency of the rhythmic oscillations generated by geniculate neurons is controlled by the patterns of activation of corticothalamic inputs, which in these experiments were mimicked by electrical stimulation of corticothalamic fibers (92). Accordingly, several studies in genetic rodent models of absence seizures have revealed changes in neocortical excitability, including increased non-N-methyl-Daspartate (NMDA)-and NMDA-receptor mediated excitatory synaptic transmission (74,89,90) and decreased GABA-mediated inhibition (89,93). Overall, the expression of generalized spike-and-wave discharges during absence seizures in most animal models requires the function of reciprocally connected thalamic and cortical networks.…”
Section: Fig 3 a Bmentioning
confidence: 99%